Studi Pengaruh Variasi Konsentrasi Garam Dapur (NaCl) sebagai Larutan Elektrolit dan pH Bahan Baku dalam Pembuatan Biobaterai Kering Berbasis Limbah Kulit Pisang Kepok - Sarah, Maya; Zelfi, Elfina Rahmania; Kuswara, Marisa Pancar; Hasibuan, Isti Madinah (Talenta Publisher (Universitas Sumatera Utara), 2024)
Batteries are single-use energy. Battery waste disposed on the ground will produce waste that is difficult to decompose naturally. Batteries contain chemicals that are toxic to soil fertility, such as potassium and sodium. One way to utilize battery waste is to turn it into bio-batteries. This research aims to minimize the waste of batteries and kepok banana peels that are underutilized by making environmentally friendly bio-batteries. This study also determines the voltage, current, and power of kepok banana skin-based bio-batteries. The method used is to conduct biobattery trials using paste from kepok banana peels. The results showed that kepok banana peels could conduct electricity to be used as a paste for bio-battery. The most significant voltage generated is 1.38 volts, while the largest current generated is 0.95 A. This bio-battery can last an average of 3 days 8 hours or 92.5 hours.